The Effect of Single Leg and Double Leg Bounding Exercise Program (BEP) on Increasing the Physical Ability of Agility, Strength, Balance and Leg Muscle Power - Mohammad Zaim Zen; Hari Setiono; Nining Widyah (Britain International for Academic Research (BIAR) Publisher, 2021)
The objectives of this study are to study and test the effect of using the effect of the single leg and double leg bounding exercise program (BEP) on the improvement of physical agility, strength, balance, and leg muscle power. The subjects of this study were 42 students of Physical Education class 2017 STKIP PGRI Jombang.This type of research is quantitative with quasi-experimental techniques. Sampling using the Solvin formula and purposive sampling technique. The process of taking data from the initial test and the final test uses the leg dynamometer test to determine leg muscle strength, side step test for agility, force plate test for leg muscle power, and balance beam test for balance.The results of the study on the normality and homogeneous tests showed normal and homogeneous data results with a significance value above 0.05. The mean difference test was carried out using the paired test and the Manova test. The method of increasing the agility, strength, balance and leg muscle power has a significant improvement with the two experimental methods.The conclusion of this study is that the bounding exercise program can significantly increase the agility, strength, balance and leg muscle power. However, from the two exercises the increase was greater in the group using the single leg bounding type of exercise.